AKSELERASI PENINGKATAN KOMPETENSI PENDIDIK DAN TENAGA KEPENDIDIKAN NONFORMAL - Mulyana, Enceng (JIV-Jurnal Ilmiah Visi, 2007)
This article discusses various steps to increase the competence of PTK-PNF. First, it describes the roles of non-formal education in the national education system and the existing problems in the non-formal education. Then, the strategies to accelerate the competencies of PTK-PNF are introduced to cover the basic competencies and mapping of PTK-PNF. Further, the model of acceleration and need analysis to improve the competencies of PTK-PNF and the model of controlling the quality of the competence are elaborated and a set of controlling principles are identified. The article concludes that accelerating the competencies of PTK-PNF is an urgent need and can not be avoided to achieve the objectives of national education. This could be done through pre-service training, inand on-service trainings or distance learning programs. Total Quality Management and Professional Approach are recommended to be implemented continuously in each program.